PREVALENSI DAN GAMBARAN KARAKTERISTIK OBESITAS SENTRAL PADA ANAK SEKOLAH DASAR DI KECAMATAN BANYUMANIK KOTA SEMARANG 2018 - Nabila Yasminuljannah Rahmani; Ari Udiyono; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In Banyumanik District, Semarang City, there was not central obesity prevalence at the age of elementary school children. In fact, central obesity at this age is known to have a risk of developing disease due to the risk of metabolic syndrome. The purpose of this study was to determine the prevalence of central obesity at school age and its potrayed based on age, sex and nutritional status based on the standard of child growth by WHO. Body weight, height and waist circumference were measured in 1686 elementary school children in Banyumanik Subdistrict, Semarang City (male as many as 871 children). WHO AnthroCalc Plus is used to determine the nutritional status of children based on the z-score Body Mass Index. Central obesity is defined by waist-to-height-ratio ≥ 0.5. Univariate analysis was used to determine the distribution of respondents based on age, gender, nutritional status and central obesity status. The cross tabulation table was used to determine the proportion of central obesity in the variables of age, sex and nutritional status. The results of the study showed that the central obesity prevalence in public elementary school children in Banyumanik District was 20.70%. Men have a higher prevalence (22.0%) than women (19.3%). Central obesity was found in children with thin, normal, overweight and obese nutritional status with a proportion of 1.6%, 2.2%, 39.5% and 89.2%. The conclusions of this study are that central obesity occurs in primary school-aged children in Banyumanik Subdistrict, Semarang City. The prevalence of central obesity in boys is higher than females. Researchers recommend measuring central obesity in children to be able to control and prevent risk factors for developing metabolic syndrome.